2019
DOI: 10.21203/rs.2.18489/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of plasmid-mediated AmpC beta-lactamases in Enterobacteria isolated from urban and rural folks in Uganda

Abstract: Background: AmpC beta-lactamases are associated with increased resistance to third-generation cephalosporins. Here, we describe plasmid-mediated AmpC beta-lactamase-producing enterobacteria isolated from urban and rural dwellers in Uganda. Methods: Stool and urine from 1,448 individuals attending outpatient clinics in Kampala and two rural districts in central Uganda (Kayunga and Mpigi) were processed for isolation of Escherichia coli and Klebsiella. Following antibiotic susceptibility testing, cefoxitin resis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…A number of studies have shown different prevalence of K. pneumoniae among isolates determined in different study places putting it at around 3% to 12%; 3% [40], 5% [41]. The prevalence rate of Klebsiella pneumoniae was at 12.57% in this study which is in the agreement with the previous study done at MRRH…”
Section: Prevalence Of K Pneumoniaesupporting
confidence: 90%
See 1 more Smart Citation
“…A number of studies have shown different prevalence of K. pneumoniae among isolates determined in different study places putting it at around 3% to 12%; 3% [40], 5% [41]. The prevalence rate of Klebsiella pneumoniae was at 12.57% in this study which is in the agreement with the previous study done at MRRH…”
Section: Prevalence Of K Pneumoniaesupporting
confidence: 90%
“…Prevalence was higher in Females (63.43%) than in the Male (36.57%) due to mechanical, hormonal and physiological changes at adolescence, during pregnancy and pre/post menopause. Females who were 50 years of age and above were found to be more infected with Klebsiella spp associated infection probably due to reduced immunity and pre/post menopause whereas Males between 18 and 50 years of age had the highest incidence of infection on age group greater than 50 years due to poor health living styles like increased sexual activities and living a dangerous life which is much supported by a number studies done around [40] [46].…”
Section: Distribution Of Klebsiella Spp Among Different Specimens Agmentioning
confidence: 88%